Literasi Kesehatan Guru PAUD tentang Pertumbuhan dan Perkembangan Anak - iman sari, Asri; Trianggaluh Fauzia, Dina; Dwi Hapsari, Indria (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Increasing the health literacy of PAUD teachers through consolidating health literacy using Maternal and Child Health (KIA) books. Monitoring children's growth and development can be done using the KIA book as an instrument or tool for monitoring children's growth and development. This program is carried out at PAUD Al Muttaqin, Jember Regency, involving PAUD teachers as the main partners in monitoring children's growth and development activities. Training and mentoring is provided to PAUD teachers to improve their ability to regularly monitor children's health and collaborate with health workers and parents. It is hoped that this program will be able to improve health management in PAUD, improve monitoring of child growth and development, and contribute to reducing stunting rates. Apart from that, this program also provides learning experiences for students within the framework of the Independent Learning Campus.